2006
DOI: 10.1111/j.1445-6664.2006.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isothiocyanates on purple (Cyperus rotundus L.) and yellow nutsedge (Cyperus esculentus L.)

Abstract: Purple and yellow nutsedge are two of the most troublesome weeds in the world. In the south‐eastern USA, both weeds are common in vegetable crops and are the most difficult weeds to control in this region. A greenhouse experiment was conducted to evaluate the herbicidal activity of five liquid isothiocyanates (ITCs) (benzoyl, o‐tolyl, m‐tolyl, tert‐octyl, and 3‐fluorophenyl) on purple and yellow nutsedge. All ITCs were applied to soil in jars at 0, 100, 1000, 5000, and 10 000 nmol g−1 of soil and sealed for 72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Allelopathy and increased Pythium populations could also explain decreased survival of transplanted muskmelon. While Pythium impacts many crops, plants have been shown to vary in their vulnerability to brassica cover crops (Norsworthy et al, 2006;Oleszek, 1987). While this work did not test for the presence of Pythium in the experiment, it is likely that allelopathy played a major role in the low emergence of muskmelon.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Allelopathy and increased Pythium populations could also explain decreased survival of transplanted muskmelon. While Pythium impacts many crops, plants have been shown to vary in their vulnerability to brassica cover crops (Norsworthy et al, 2006;Oleszek, 1987). While this work did not test for the presence of Pythium in the experiment, it is likely that allelopathy played a major role in the low emergence of muskmelon.…”
Section: Discussionmentioning
confidence: 93%
“…Haramoto and Gallandt (2005) determined that brassica cover crops decreased cash crop emergence by 23% to 34% and delayed germination 2 d, although their impact was similar to that of other short-season cover crops such as red clover (Trifolium pratense); cash crops tested in the study included carrot (Daucus carota), tomato (Solanum lycopersicum), and cucumber. Laboratory experiments have shown that compounds produced by brassica cover crops can inhibit weed seed germination Meehan, 2005a, 2005b;Norsworthy et al, 2006). Studies with black mustard (Brassica nigra) aqueous extracts have shown that extracts inhibit germination and growth of lentil (Lens culinaris) and wild oat (Avena fatua) Tawaha, 2002, 2003).…”
mentioning
confidence: 99%
“…ITCs showed allelopathic effects on wheat (Bialy et al, 1990;Vaughn and Berhow, 1999). The shoot density of many weed species was reduced by the application of ITCs (Yamane et al, 1992;Norsworthy and Meehan IV, 2005;Norsworthy et al, 2006). It is estimated that green manures consisting of ITC-producing plants are promising bioherbicides for use in integrated pest management strategies (Brown and Morra, 1995;Vaughn and Boydston, 1997;Gimsing and Kirkegaard, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous extracts of winter rape (Brassica napus) shoots inhibited lettuce (Lactuca sativa) seed germination (Brown and Morra, 1996). Similarly, hemp sesbania (Sesbania herbacea) germination and fresh weight were reduced greater than 95% by isothiocyanates released from chopped leaves of Brassica species (Vaughn and Boydston, 1997 nutsedge emergence and shoot production in purple and yellow nutsedge (Norsworthy and Meehan, 2005c;Norsworthy et al, 2006). According to Uremis et al (2009), herbicide applications to control johnsongrass (Sorghum halepense) can be reduced by incorporating crucifer green manure in soil before planting a commercial crop.…”
mentioning
confidence: 99%